PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PATRA KOMALA DI DUMAI - Sari, Yanti Komala (Jurnal Tepak Manajemen Bisnis, 2014)
This study aims to determine the factors Kepemimpinanan , Motivation and Workplace PerformanceAgainst Discipline Employee Performance at PT . Patra Komala In Dumai . This research was conducted at PT. Komala patra Dumai . Target population are employees of PT Patra Komala Dumai totaling 65 people ,conducted a census / saturation sampling that samples taken by the amount of the overall population . So thesamples in this study were as many as 65 employees .The object of research as a factor of independently variableis Leadership , Motivation , Disilin work . While the dependent variable is Employee Performance . Hypothesistesting is performed using Multiple Regression Analysis Model .The results showed that the partial or t test of each variable only variables significantly influence the performanceleadership of this can be seen from the variable Kepemiminan of 2,935 is greater than t table 1.66 , while themotivation variable and variable work discipline had no significant effect where the t test smaller than t table is0.852 ( motivation ) and 0.453 ( work discipline ) and F test or simultaneous factor Leadership , motivation , andwork discipline of 17.651 direct and significant impact on Employee Performance PT . Komala patra Dumai.It can be concluded that simultaneous Leadership , Motivation and discipline are jointly significant effect on theperformance variables . While only partially leadership variables significantly influence employee performance .From these results suggested to the management company can create leadership , motivation and discipline of workthat can be accepted by all parties that can provide a good solution for the development and progress of the PT . PatraKomala .Keywords : Leadership , Discipline , Motivation , Performance